More than just a bunch of bones: the meaning of silence in Gloria Anzaldúa - Ortiz, Mariana Itatí (Millcayac - Revista Digital de Ciencias Sociales, 2025)
The article addresses the conceptualization of silence in the work of Gloria Anzaldúa, manifesting in a serpentine and, at times, like a fugitive sense. Explored as a liminal space and a battleground, it retrieves contributions from radical geography and the artistic field for analysis, particularly within contemporary performing arts. From these contributions, it investigates the meaning of the image within them, serving as a bridge for the production of knowledge from which to narrate experiences and heal colonial wounds.